2018
DOI: 10.1038/s41430-018-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and clinical course of multiple sclerosis

Abstract: The Dietary Inflammatory Index did not affect the clinical condition of individuals with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Using less food parameters generally also results in a lower variation in DII [ 11 ]. However, all other studies that calculated the DII also were unable to include all 45 food parameters and used a number of food parameters that was comparable to our study [ 12 14 , 20 , 21 ]. The DII only consists of food parameters, supplement use is not included.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using less food parameters generally also results in a lower variation in DII [ 11 ]. However, all other studies that calculated the DII also were unable to include all 45 food parameters and used a number of food parameters that was comparable to our study [ 12 14 , 20 , 21 ]. The DII only consists of food parameters, supplement use is not included.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, it is likely that the DII better reflects the influence of diet on inflammation and thus on the course of disease than analyses with single foods [ 9 11 ]. The DII has been used in several other patient groups to predict the dietary inflammatory potential related risk for development of disease or the influence on clinical course of disease [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is only one cross-sectional study that has examined this and they found no association between the DII and relapse rate in the previous 2 years (p = 0.433). 10 When we assessed the DII scores in relation to lesion volume, we found that a higher DII was associated with a higher FLAIR lesion volume in the periventricular legion with evidence of a dose-response and consistency with E-DII. While no clear associations were seen in the total sample, the associations strengthened somewhat when we limited to those with the same scanner (i.e.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, it was reported that DII was not significantly associated with the clinical condition of individuals with MS (50) . Moreover, Silva et al (51) , in a cross-sectional study, reported that DII does not correlate to waist circumference, waist-hip ratio, body roundness index, body shape index, body shape z score index and percentage of body fat among MS patients.…”
Section: Discussionmentioning
confidence: 97%